Legal Document Planning At Kyan’s Cafe - Della Fairly; Evi Silvana Muchsinati (Universitas Internasional Batam, 2023)
Kyan''s cafe has been operating for a long time but the café does not implement a work contract system which is useful for clarifying the status of employees working at the café, applying legal documents for example work contracts or regulations in business are also very important and both parties can also work well with a binding agreement work. This led to the turnover rate in the past year.The data collection technique carried out by the executors in the process of implementing the Student creativity program is research in the field by making direct observations in the field. In addition, the executor also conducts interviews directly with the café owner to find information and provide the right data that can help the executor resolve the existing problems. This work agreement letter aims to help make it easier for the owner to fulfill the wishes of the employee without making a decision that is contrary to the employee